Price Transparency in the Management of Skull Base Tumors—The Price to Operate - Patel, Shrey; Mastropierro, Julianna; Spagnuolo, Genevieve; Kosarchuk, Jacob; O'Brien, Monica; Wu, Julian; Heilman, Carl; Noonan, Kathryn (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Due to the escalating health care costs in the United States, the Centers for Medicare and Medicaid Services (CMS) implemented a cost transparency initiative on January 1, 2021. Hospitals lack functional cost estimators or fail to provide pricing information for common skull base procedures.Methods A list of the top 70 neurosurgery and otolaryngology hospital systems according to the US News and World Report rankings was made. Google searches for each hospital's cost estimator tool were conducted, recording its presence and accessibility time. Using the cost estimator tool, specific skull base procedure prices, Current Procedural Terminology codes, and contact information for personalized estimates were searched.Results Fifty-seven hospitals (81%) were privately funded. The majority were urban teaching hospitals (n = 68; 97%). Geographical locations included 19 (27%) in the Northeast, 21 (30%) in the Midwest, 20 (29%) in the South, and 10 (14%) in the West. Of the 70 hospitals, 4 (5.7%) did not have a cost estimation website. Of the 66 hospitals that did, the average time to locate the cost of the skull-based procedures was 17.8 seconds (range 12–28 seconds). Only two (2.9%) hospitals had information for skull base procedures; both were radiosurgery procedures. The most common stereotactic radiosurgery offered was gamma knife radiosurgery (n = 50; 71%). A total of 19 hospitals (27%) did not include contact information for personalized cost estimation.Conclusion The CMS price transparency guidelines are not designed to encompass skull base procedures. Due to this ambiguity, patients are unable to make informed financial decisions when selecting treatment options.
Keywords: skull base; cost; financial service; vestibular schwannoma; CMS